KIBRA (WWC1) Is a Metastasis Suppressor Gene Affected by Chromosome 5q Loss in Triple-Negative Breast Cancer - Jennifer F. Knight; Vanessa Y.C. Sung; Elena Kuzmin; Amber L. Couzens; Danielle A. de Verteuil; Colin D.H. Ratcliffe; Paula P. Coelho; Radia M. Johnson; Payman Samavarchi-Tehrani; Tina Gruosso; Harvey W. Smith; Wontae Lee; et al. (Cell Reports, 2018)
Summary: Triple-negative breast cancers (TNBCs) display a complex spectrum of mutations and chromosomal aberrations. Chromosome 5q (5q) loss is detected in up to 70% of TNBCs, but little is known regarding the genetic drivers associated with this event. Here, we show somatic deletion of a region syntenic with human 5q33.2–35.3 in a mouse model of TNBC. Mechanistically, we identify KIBRA as a major factor contributing to the effects of 5q loss on tumor growth and metastatic progression. Re-expression of KIBRA impairs metastasis in vivo and inhibits tumorsphere formation by TNBC cells in vitro. KIBRA functions co-operatively with the protein tyrosine phosphatase PTPN14 to trigger mechanotransduction-regulated signals that inhibit the nuclear localization of oncogenic transcriptional co-activators YAP/TAZ. Our results argue that the selective advantage produced by 5q loss involves reduced dosage of KIBRA, promoting oncogenic functioning of YAP/TAZ in TNBC. : Triple-negative breast cancers (TNBCs) frequently lose chromosome 5q. Using a TNBC mouse model with spontaneous loss of a syntenic region, Knight et al. identify KIBRA as a metastasis suppressor. Mechanistically, KIBRA suppresses RHOA activation, impairing nuclear translocation of the oncogenes YAP/TAZ, which drive metastatic and cancer stem cell-like behavior. Keywords: KIBRA, WWC1, PTPN14, YAP/TAZ, mechanotransduction, RHOA signaling, triple-negative breast cancer, metastasis, tumorspheres, chr5q